Encouraging Sustainable Development With Green Tax Credit Policy - Dinata, I Putu Hendy Bimantara; Firmansyah, Amrie (WIM Solusi Prima, 2024)
Climate change is an issue that is currently of concern to various parties. Many studies reveal that climate change can have an adverse impact on various aspects of human life. Therefore, various countries have issued policies to encourage sustainable development to mitigate the effects of climate change. This research examines the implementation of the green tax credit policy in Indonesia as a form of government effort to encourage sustainable development. This research discusses the proposed scheme, benefits, and challenges of implementing green tax credit policy in Indonesia. A qualitative method with a literature study and scoping review is used in this research. The analysis method used in this research is descriptive qualitative. The results of this study show that the green tax credit scheme provides numerous benefits, such as being more universal, being implemented easily, and encouraging sustainable development in the long term. The challenges of implementing this policy are decreased tax revenue, monitoring costs, and resistance from certain parties. Seeing the benefits of green tax credits in promoting sustainable development, the government can consider implementing this policy in Indonesia.